Difference in maximum number of repetitions performed by practitioners of Jiu-Jitsu in bench press horizontal using intervals between series - Mazini Filho, Mauro Lúcio (2014)
The interval is relevant variable resistance training, being quite important adequately implemented during the training period in which the goal is maximum strength gains. The aim of the study is to evaluate the use of 90% of 1-RM as the training zone for increased maximum force to investigate the effects of two intervals (2:5 minutes) the maximum number of repetitions performed over three series in supine horizontal. As you examine the study, the maximum number of repetitions performed under each series, regardless of the time interval: 1st series (2 min.: 5.9 ± 1.0 repetitions; 5 min.: 6.3 ± 1, 2 repetitions), grade 2 (2 min.: 3.9 ± 1.1 repetitions; 5 min.: 4.8 ± 1.4 reps) and grade 3 (2 min.: 2.8 ± 0.9 repetitions; 5 min.: 3.5 ± 1.4 repetitions). The total volume of repetitions achievedshown lower with 2 min. interval (12.6 ± 2.6 repetitions) compared to 5 min. (14.6 ± 3.6 repetitions). It was found that the 5-minute interval provided better recovery between sets of horizontal supine than an interval of 2 minutes.